Streptococcal superantigen-induced expansion of human tonsil T cells leads to altered T follicular helper cell phenotype, B cell death, and reduced immunoglobulin release - Davies,FJ; Olme,C; Lynskey,NN; Turner,CE; Sriskandan,S (2018)
Abstract Background Streptococcal pyrogenic exotoxin (SPE)A expression is epidemiologically linked to streptococcal tonsillo-pharyngitis and outbreaks of scarlet fever, although the mechanisms by which superantigens confer advantage Streptococcus pyogenes are unclear. S. pyogenes is an exclusively human pathogen. As the leukocyte profile of tonsil differs from peripheral blood, the impact of SPEA production on human tonsil cell function was investigated. Methods Human tonsil cells from routine tonsillectomy, were co-incubated with purified streptococcal superantigens or isogenic streptococcal culture supernatants, differing only in superantigen content. Tonsil cell proliferation was quantified by tritium-incorporation, and cell surface characteristics assessed by flow-cytometry. Soluble mediators were measured using ELISA and quantitative (q)RT-PCR was performed for immunoglobulin gene expression. Results Tonsil T cells proliferated in response to SPEA and demonstrated typical release of pro-inflammatory cytokines. When cultured in the absence of superantigen, tonsil preparations released large quantities of immunoglobulin over 7d. In contrast, marked B cell apoptosis and abrogation of total IgA, IgM, and IgG production occurred in the presence of SPEA and other superantigens. In SPEA-stimulated culture